Retrospective prophecy and medieval English authorship - Fonzo, Kimberly (University of Toronto Press, 2022)
"This study argues that prophecy emerged and recurred as an important theme in both medieval authorial self-representation and the subsequent intellectual and critical assessment of medieval authors and their works by others. Because prophecy is always a second hand authority, readers can be easily coopt it to support their own political and theological causes. The author examines three English authors whose reputations have been appropriated in a variety of ways due to the prophetic portions of their texts (or texts that have been attributed to them)--William Langland, John Gower, and Geoffrey Chaucer."--